China in Africa: Phoenix nests versus Special Economic Zones - (:unkn) unknown (My University, 2019)
Many articles and studies introduce special economic zones (SEZ) as the solution that would boost Africa’s development. In this Occasional Paper we will not discuss the accuracy of this vision. We will only ask whether the model of Overseas Economic and Commercial Cooperation Zones (OECCZ) that China is proposing to African countries – as well as those along the New Silk Roads – matches the definition of a SEZ as understood by Chinese researchers and commentators themselves. At this stage of our research, the most accurate answer could be Lin Yifu’s for whom establishing an OECCZ is above all “building a nest to accommodate the Phoenix” [筑巢引凤 zhu chao yin feng] – i.e. China – without much consideration for the actual needs of the countries hosting these OECCZs.
Keywords: African Research